(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
This paper will discuss how plastic-contaminated native soil microbial consortia contained in the state of Anambra, Nigeria can be used to biodegrade plastic (PE) and polyethylene terephthalate (PET) waste materials. The main aim is to identify and describe these consortia, determine its degradation performance at both laboratory and field setup and establish an initial bioremediation procedure. Three locations, namely a landfill site in Onitsha, a dumpsite in Awka and an industrial area in Nnewi were used as the locations of soil sampling which consisted of 30 samples at 0-20 cm depth of the soil in each site. Isolation of microbes entailed enrichment cultures under PE and PET as the only carbon sources and thereafter, 16S rRNA and ITS sequencing was done. Degradation was measured through an 60 days incubation by weight loss and by products GC-MS study. Mesh bags were used in in-situ assessment. Findings determined six consortia, the majority of which included Bacillus spp., Pseudomonas spp., and Aspergillus spp., which produced PE and PET with 12-18% and 10-15% weight loss, respectively, which the ANOVA verified as site-specific. Field degradation achieved 8-12 hence applicability. Intermediates that were identified by GC-MS included aldehydes and carboxylic acids, which were indicators of oxidative pathways. The research paper is relevant to microbiology because it emphasizes the microbial diversity of an area to manage waste sustainably, and it suggests a scalable approach to Nigeria. Limitations are that the incubation period is not very long and that the environmental variables may be hazardous, in future research genetic engineering ought to be researched on so as to make better use of it. On the whole, the indigenous consortia are a promising and environmentally-friendly way of solving plastic pollution in developing areas.